Effect of watermelon rind powder on physicochemical, textural, and sensory properties of wet yellow noodles - Ho, Lee Hoon; Norhidayah, Dahri (Taylor and Francis Ltd., 2016)
The physical, chemical, and sensorial properties of the control noodle (WRP0), noodles incorporated with watermelon rind powder (WRP) at the levels of 50, 100, and 150 g/kg (WRP5, WRP10, and WRP15, respectively), were investigated. Ash, crude fiber, crude fat, carbohydrate, and total phenolic content (TPC) of WRP-containing noodles increased gradually on increasing the level of replacement compared to the control. However, a decreasing trend was observed in moisture and protein contents. Incorporation of WRP in noodles did not affect the lightness value and cooking yield. However, the yellowness and greenness indices increased gradually on increasing the level of powder substitution compared to the control. A decreased trend was observed for the firmness, cooking loss, and pH values on increasing the level of replacement. Sensory evaluation results showed that WRP10 had the highest acceptability.